Hukum Ekonomi dan Pembangunan Berkelanjutan: Studi Kasus di Negara-Negara ASEAN - Akbar, Ikhsanul; Ningrum, Indriani Septia; Muzhaffar, Rafi; Irawan, Aryo; Fayza; Atmaja, M. Toriq Raka; Siswajanthy, Farahdinny (Indonesian Journal of Law and Justice, 2024)
Economic law and sustainable development are two interrelated concepts that influence public policies in ASEAN countries. This research aims to analyze the relationship between economic law and sustainable development in ASEAN countries, as well as the challenges and opportunities faced by these countries in implementing the principles of sustainable economic law. The research method used is a normative juridical approach, namely by examining laws and regulations, official documents, and related literature relating to economic law and sustainable development in ASEAN countries. The results show that there are variations in the level of engagement and commitment of ASEAN countries in realizing economic law and sustainable development, depending on factors such as social, political, economic, and environmental conditions in each country. The research also identifies several important issues that need to be addressed by ASEAN countries, such as the need for legal harmonization, enhanced regional cooperation, protection of human rights, community empowerment, and effective law enforcement. This research provides recommendations to improve the quality and effectiveness of economic law and sustainable development in ASEAN countries, and its implications for social welfare and justice in the region.